Defining Permanency for Aboriginal Youth in Care - Stangeland, Jade; Walsh, Christine (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Poor outcomes associated with youth aging out of care are well documented. In recent years creative permanency planning projects have been heralded as promising alternatives to transition to adulthood programs with the aim of addressing this concern. In order to make permanency possible for youth the concept must be defined in a way that reflects the needs of those within this developmental stage. Researchers and youth have collaborated to create such definitions. However, few have considered a cultural element and none speak to specific populations, such as Aboriginal youth. There are significant differences between Western and Aboriginal worldviews, which, in turn, influence the permanency, need for children and youth. In Alberta, Canada, Aboriginal children and youth are vastly overrepresented in out-of-home care. Addressing the needs of Aboriginal youth in a culturally appropriate manner is critical. Cultural considerations include ideals of collectivism versus individualism, identity formation, and community healing. Yet, there is a deficit of literature related to the specific permanency needs of Aboriginal youth in out-of-home care. The Ecological theory informed by the Anishinabe medicine wheel framework provides a structure from which to discuss permanency planning for this population group. Further research exploring the views of Aboriginal youth in care on permanency and the utility of these models on this population is necessary.